Implementing the Principles of Good Governance at the Office of the Investment and Integrated One-Stop Service Agency in South Sulawesi Province - Fitriani Fitriani; Muhammad Guntur; Andi Aslinda (Universitas Negeri Makassar, 2023)
This study aims to examine the implementation of Good Governance-based services in the Investment and Integrated One-Stop Service Agency of South Sulawesi Province. This research is a qualitative descriptive study. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis techniques used consisted of data reduction, data presentation, and conclusion drawing. The focus of this research is on the implementation of the principles of good governance, which refer to five indicators: Accountability, Transparency, Rule of Law, Responsiveness, and Effectiveness and Efficiency. Based on the research findings, it is known that in terms of accountability, the rule of law, responsiveness, and effectiveness and efficiency, the standards have been met. The accountability principle is considered good because the agency has operated according to the plan and continuously evaluates and reports accountability. The rules and regulations regarding employees are also sufficiently strict. The responsiveness to public complaints is also good, as evidenced by the existence of a complaint section that accommodates all public grievances. The services provided are considered effective and efficient because they are in line with the conditions and capabilities of both the service provider and the recipient, which greatly facilitates the public. However, in terms of transparency, the standard has not been met as the time and procedures do not adhere to the applicable service standards.